Prosocial Identities and Youth Violence. (February 2019) - Na, Chongmin; Paternoster, Ray
Objective: Despite a recent surge of interest in the important role that identity change plays in the desistance process, much of the empirical work has been qualitative and conducted with small samples, usually of serious adult offenders. Drawing on a nationally representative sample of adolescents in South Korea, this study explores how the development of their prosocial identity is related to their own social bond and network and collectively how this process relates to a downward trend in violent behavior. Method: Negative binomial random effects models were estimated to assess the within-individual effects of the proposed predictor and mediators on the outcome variable. Then, longitudinal path analyses were conducted to explore the overall and specific mediation processes. Conclusion: First, there is an inverse relationship between prosocial identity and violent behavior across time. Second, our own identity of self might not be entirely a social construction based on others' appraisals but is intimately connected to the actions that we intentionally take. Third, positive effects of a prosocial identity on subsequent violence are mediated primarily by the avoidance of association with delinquent peers. Theoretical implications and limitations are discussed.